STUDI PERBANDINGAN SIFAT MEKANIK BAJA ABRASIVE RESISTANT CAST STEEL (ARCS) DAN SCMNH11 UNTUK APLIKASI HAMMER LIMESTONE CRUSHER : COMPARATIVE STUDY OF MECHANICAL PROPERTIES OF ABRASIVE RESISTANT CAST STEEL (ARCS) AND SCMnH11 FOR HAMMER LIMESTONE CRUSHER APPLICATION - franciskus edy prasetiawan; Anggoro Harry Sulistyawan; Nudito Rifqi Himawan (Jurnal Teknik Mesin, 2026)
This study compares two materials, namely Abrasive Resistant Cast Steel (ARCS), a type of abrasion-resistant cast steel designed for industrial applications exposed to severe abrasive conditions, and SCMnH11, a high-manganese steel commonly used for hammer applications in limestone crushers within the cement industry. The research focuses on analyzing mechanical properties such as tensile strength, yield strength, hardness, as well as the chemical composition and microstructure of both materials. The results show that ARCS exhibits superior tensile and yield strength compared to SCMnH11, with respective values of 923 N/mm² and 756 N/mm², while SCMnH11 demonstrates higher elongation (25%) compared to ARCS (9.5%). In terms of hardness, SCMnH11 is harder (30 HRC) than ARCS (25.6 HRC). Chemical analysis indicates that SCMnH11 has a higher manganese content (9.08%) than ARCS (1.32%), contributing to its toughness, whereas ARCS contains more chromium (2.25%), enhancing its wear resistance. Microstructural analysis reveals that ARCS consists of a combination of bainite and ferrite, providing strength and hardness, while the austenitic structure of SCMnH11 enables it to absorb impact more effectively without damage.